In Vitro Regeneration of Three Gladiolus Cultivars Using Cormel Explants - Kurniawan Budiarto (Jurnal ILMU DASAR, 2009)
In vitro technique was dedicated to alleviate the technical problems in conventional propagation of gladiolus for healthy planting material production in marketable quantities.  Two experimental series were conducted in non factorial and factorial designs respectively.  Cormels of three gladiolus cultivars namely Kaifa, Clara and Nabila were inoculated into free hormone media for plantlet establishment and dormancy breaking observations among genotypes.  The established plantlets were then deflasked into solidified MS + 0.5 mg/l NAA with various BA concentrations (1, 2, 3 and 4 mg/l).  A randomized complete experiment with seven replications was designed to accomplish these subsequent experiment to determine optimal BA for shoot-leaves initiations and complete plantlet formations. The results showed that in free hormone media, the dormancy breakings of cormel were varied among cultivars tested.  The variation among cultivars was also detected on the level of BA for optimum shoot and leaf formations.  2 mg/l BA gave highest shoot and leaves formations for cv. Nabila while higher concentrations needed by other two cultivars. Thus, BA concentrations ranged from 2–3 mg/l were recommended shoot inductions on in vitro propagation of gladiolus.